2013 IEEE International Conference on Healthcare Informatics 2013
DOI: 10.1109/ichi.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Mining Association Rules for Neurobehavioral and Motor Disorders in Children Diagnosed with Cerebral Palsy

Abstract: Children diagnosed with cerebral palsy (CP) appear to be at high risk for developing neurobehavioral and motor disorders. The most common disorders for these children are impaired visual-perception skills and motor planning. Besides, they often have impaired executive functions, which can contribute to problematic emotional adjustment such as depression. Additionally, literature suggests that the tendency to develop these cognitive impairments and emotional abnormalities in pediatric CP is influenced by age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Similarly, our findings indicated children with cerebral palsy and a history of seizures showed slower‐than‐expected development of FSIQ over time. This is consistent with previous studies that suggest seizures have a deleterious effect on cognition 26,27 . Indeed, there is an interplay between age, seizures and cognitive abilities—that is, an adolescent with cerebral palsy and seizures is more likely to have lower IQ than a younger child with cerebral palsy and seizures 26 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, our findings indicated children with cerebral palsy and a history of seizures showed slower‐than‐expected development of FSIQ over time. This is consistent with previous studies that suggest seizures have a deleterious effect on cognition 26,27 . Indeed, there is an interplay between age, seizures and cognitive abilities—that is, an adolescent with cerebral palsy and seizures is more likely to have lower IQ than a younger child with cerebral palsy and seizures 26 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies that suggest seizures have a deleterious effect on cognition. 26,27 Indeed, there is an interplay between age, seizures and cognitive abilities-that is, an adolescent with cerebral palsy and seizures is more likely to have lower IQ than a younger child with cerebral palsy and seizures. 26 This contention is supported by MRI studies, which have shown that increasing epilepsy duration is associated with reduced efficiency of brain networks that support higher order cognitive functions 28,29 and in turn, is associated with IQ decline.…”
Section: Level IIImentioning
confidence: 99%
See 1 more Smart Citation
“…ARM has been widely used in data mining for the discovery of new and potentially important relationships among variables in biomedical and healthcare domains such as gene expression profiling [20, 21], cardiovascular disease prediction [22, 23], healthcare auditing [24, 25], neurological diagnosis [26, 27], and predictive health [28]. In our previous study, we developed an ICU clinical decision support system (named icuARM ) using ARM and MIMIC-II, which is a well-known ICU research database [29].…”
Section: Temporal Association Rulesmentioning
confidence: 99%